Cultural Transplantation and Legal Paradox: The Case of the Indonesian Judicial Commission Versus the Supreme Court - JM Muslimin (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2021)
The purpose of this research was to prove that solving a legal problem needed an interdisciplinary approach, more than merely pure law. It relates to the working culture of law, inter-subjective understanding and reform willingness. The research was done based on descriptive and qualitative method. It included content analyses of the use and misuse concept of regulation, its effect in actual practice and cultural barrier of law enforcement. The finding of this research proved that law enforcement was not like copying a paper. It related closely to the tradition, usage and custom of people. Transforming society only by introducing new regulation and state institution without cultural restoration ended in failure. Thus, the conclusion was the establishment of Judicial Commission in Indonesia, aimed at transforming the Supreme Court, to be more independent, impartial and accountable by supervising the ethical behaviour of the judge. But Judicial Commission is hampered by many difficulties legally and institutionally. Judicial Commission could not work and achieve its goal to bring about Supreme Court more transparent, not only because of legal obstacles but also cultural impunity.